Gender Inequality and Economic Development - Khayria, Karoui; Feki, Rochdi (My University, 2015)
This article attempts to analyze the effect of gender inequality on economic growth using the GMM dynamic panel for the five countries of the Great Maghreb during the period 1985-2011.The results of this study lead us to demonstrate, one hand, a positive and significant at the 5% of the population effect on economic growth and on the other hand a statistically significant and negative in 10% of the investment on economic growth effect. In contrast, gender inequality has a significantly negative effect of 5%.
Keywords: Gender inequality; Economic growth; Panel data